2001
DOI: 10.1111/1471-0366.00009
|View full text |Cite
|
Sign up to set email alerts
|

Telling Environmental Change Like It Is? Reflections on a Study in Sub‐Saharan Africa

Abstract: This paper discusses a topical and influential approach to the study of African environments that criticizes the capacities of 'Western' science and narratives of environmental 'crisis' to comprehend patterns of environmental change and the role in them of African farmers as knowledgeable and skilled managers of the natural resources they use. We argue that this approach contains a symptomatic avoidance of processes of commoditization and differentiation in African farming which undermines its analytical value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…In dialectical interaction with technological developments and the intensification of colonial extraction (amongst other factors), emerging capitalist societies became more adept at ''offsetting'' local and regional ecological transformations extra-locally and extraregionally, hence laying the foundations for ecological crisis on a world-scale, or a ''crisis in the world-ecology,'' as Moore (2010) puts it. Across space (extensification) and within spaces (intensification), capitalism has disrupted and changed the 4 See also: Nygeres and Green (2000), Bernstein andWoodhouse (2001), Dressler, et al (2010), and Brockington (2002). There are of course many good examples of crisis; it might be apposite at this point to note that we are not climate change skeptics and have opposed the work of people like Bjorn Lomborg.…”
Section: Why Focus On Neoliberal Conservation?mentioning
confidence: 99%
“…In dialectical interaction with technological developments and the intensification of colonial extraction (amongst other factors), emerging capitalist societies became more adept at ''offsetting'' local and regional ecological transformations extra-locally and extraregionally, hence laying the foundations for ecological crisis on a world-scale, or a ''crisis in the world-ecology,'' as Moore (2010) puts it. Across space (extensification) and within spaces (intensification), capitalism has disrupted and changed the 4 See also: Nygeres and Green (2000), Bernstein andWoodhouse (2001), Dressler, et al (2010), and Brockington (2002). There are of course many good examples of crisis; it might be apposite at this point to note that we are not climate change skeptics and have opposed the work of people like Bjorn Lomborg.…”
Section: Why Focus On Neoliberal Conservation?mentioning
confidence: 99%
“…He adds that the processes identified by Berry 'need to be rooted in structures of social differentiation and class ' (1999, 44, cf. Bernstein andWoodhouse 2001). This lead will be followed in the following sections.…”
Section: Rethinking Analytical Approaches To Landmentioning
confidence: 99%
“…of household' and the tendency for any one extended family to include farmers, wage labourers, 'professionals and politicians' that makes distinctions such as 'rich', 'middle' and 'poor' peasants/ families 'necessarily arbitrary' (Raikes 2000, 68). One difference among researchers is between seeing African rural economies as 'fully capitalist' (Bernstein forthcoming;Bernstein and Woodhouse 2001), and seeing them as 'commercial without being capitalist, even while [their] dynamics link into and confront the capitalist market' (Guyer 1997, 184). In this paper, I am arguing that the current information on intensifying social conflict around land reveals deepening social differentiation and class formation.…”
mentioning
confidence: 99%
“…In a different vein, moreover, some structural Marxists have worried that newer, poststructuralist political ecology might take too much attention away from the still serious impacts of capitalism. For example, Bernstein and Woodhouse (2001) suggested 'telling environmental change as it is' should mean reverting to structuralist explanations of environmental degradation, and suggested that the deconstruction of environmental narratives by Leach and Mearns (1996) effectively romanticizes local knowledge and overlooks the impacts of commodified agriculture in Africa.…”
Section: Questions and Challengesmentioning
confidence: 99%